Home or Away: Homecoming, Glory, and the Good Death in Homer's Odyssey. Issue 1 (April 2020) - Rees, William
Abstract : This article examines the overlapping themes of the good death ( euthanasia ), glory ( kleos ), and homecoming ( nostos ) as they are deployed in Homer's Odyssey . On both a thematic and a structural level, I argue that the text stages a confrontation between homecoming and glory – between death at home and death in battle – and that this tension is a sustaining force throughout the text. In contrast to the received interpretation that sees the Odyssey as a straightforward tale of nostalgia, I argue that in Homer's epic the relation to homecoming turns out to be surprising and complex – an event that is at once painfully desired and perpetually deferred.